Understanding Factors Related to Voting for Reality Shows: A Framework of Cognitive Intermediation - Anand, Sandip (Indian Journal of Marketing, 2010)
Studies of organizations and stakeholders suggest that there is need of cognitive intermediation to create "Cognitively Just Organizations". This phenomenon is well explained by the theory of cognitive intermediation (Anand, S. 2008). According to this theory of cognitive intermediation, success of organizations or products/services seem to be dependent upon their ability to create an environment for the clients - where irrespective of the socio-economic inequality, equity at the level of cognition can be delivered in terms of respect and dignified treatment. There should be equity in the treatment given to clients in terms of dignified message. So, ability of the organizations or products/services to provide cognitive justice through cognitive intermediation by process and structure of organizations/products/services is likely to define their success. The term 'cognitive justice' has been borrowed from Visvanathan's work (Visvanathan, S. 1998, 2001). In the framework of cognitive justice, one gives equal importance to people's voice across the sections of society.